Attachment Representations and Early Interactions in Drug Addicted Mothers: A Case Study of Four Women with Distinct Adult Attachment Interview Classifications - Porreca, Alessio; De Palo, Francesca; Simonelli, Alessandra; Capra, Nicoletta (Frontiers in Psychology, 2016)
Drug addiction is considered a major risk factor that can influence maternal functioning at multiple levels, leading to less optimal parental qualities and less positive interactive exchanges in mother-child dyads. Moreover, drug abusers often report negative or traumatic attachment representations regarding their own childhood. These representations might affect, to some extent, later relational and developmental outcomes of their children. This study explored whether the development of dyadic interactions in addicted women differed based on attachment status. The longitudinal ongoing of mother-child emotional exchanges was assessed among four mothers with four different attachment statuses (F-autonomous, E-preoccupied, Ds-dismissing and U-unresolved/with losses). Attachment representations were assessed using the Adult Attachment Interview (George et al., 1985), while mother-child interactions were evaluated longitudinally during videotaped play sessions, through the Emotional Availability Scales (Biringen, 2008). As expected, the dyad with the autonomous mother showed better interactive functioning during play despite the condition of drug-abuse; the mother proved to be more affectively positive, sensitive and responsive, while her baby showed a better organization of affects and behaviors. On the other side, insecure mothers seemed to experience more difficulties when interacting with their children showing inconsistency in the ability to perceive and respond to their babies' signals. Finally, children of insecure mothers showed less clear affects and signals. While differences between secure and insecure dyads appeared clear, differences between insecure patterns where less linear, suggesting a possible mediating role played by other factors. Clinical implications and suggestions for future research are discussed.